Quantifying preferences around vaccination against frequent, mild disease with risk for vulnerable persons: A discrete choice experiment among French hospital health care workers. Issue 5 (29th January 2021) - Godinot, Léo Donzel; Sicsic, Jonathan; Lachatre, Marie; Bouvet, Elisabeth; Abiteboul, Dominique; Rouveix, Elisabeth; Pellissier, Gérard; Raude, Jocelyn; Mueller, Judith E.
Highlights: First DCE to study the drivers of health care workers' vaccination intentions. Poor vaccine safety has the most detrimental impact on stated acceptance. Indirect protection and high vaccine effectiveness are the main motivating factors. Social conformism is an important driver, while free-riding motives are rejected. Social incentives (e.g., wearing a badge " I'm vaccinated" ) are dissuasive. Abstract: The individual determinants of vaccine acceptance among health workers (HCWs) have been described in the literature, but there is little evidence regarding the impact of vaccine characteristics and contextual factors (e.g., incentives, communication) on vaccination intentions. We developed a single profile discrete choice experiment (DCE) to assess the impact of seven attributes on stated vaccination intention against an unnamed disease, described as frequent with rapid clinical evolution and epidemic potential (similar to influenza or pertussis). Attributes evaluated vaccine characteristics (effectiveness, security profile), inter-individual aspects (epidemic risk, controversy, potential for indirect protection, vaccine coverage) and incentives (e.g., badge, hierarchical injunction). A total of 1214 French hospital-based HCWs, recruited through professional organizations, completed the online DCE questionnaire. The relative impact of each attribute was estimated using random effects logit models on the whole sample and among specific subgroups. Overall, 52% of included HCWs were vaccinated against influenza during 2017–18 and the average vaccination acceptance rate across all scenarios was 58%. Aside from the management stance, all attributes' levels had significant impact on vaccination decisions. Poor vaccine safety had the most detrimental impact on stated acceptance (OR 0.04 for the level controversy around vaccine safety ). The most motivating factor was protection of family (OR 2.41) and contribution to disease control (OR 2.34). Other motivating factors included improved vaccine effectiveness (OR 2.22), high uptake among colleagues (OR 1.89) and epidemic risk declared by health authorities (OR 1.76). Social incentives (e.g., a badge I'm vaccinated ) were dissuasive (OR 0.47). Compared to HCWs previously vaccinated against influenza, unvaccinated HCWs who were favorable to vaccination in general were most sensitive towards improved vaccine effectiveness. Our study suggests that vaccine safety considerations dominate vaccine decision-making among French HCWs, while adapted communication on indirect protection and social conformism can contribute to increase vaccination acceptance.